Edentulousness, Denture Wear and Denture Needs of the Elderly in Rural South India - P Ariga; A Bridgitte; V Rangarajan; J M Philip (Tehran University of Medical Sciences, 2012)
Background: The objectives of this study were to evaluate the prevalence of edentulousness, patient's perception on dietary changes resulting from tooth loss and to identify the disparity between actual and patient perceived need to replace missing teeth in an elderly rural population in south India. Methods: A cross sectional study using the systematic cluster sampling method was used to select the study sample of 150 elderly men and women. Data were collected using questionnaires and oral examination. The data were statistically analyzed using chi square test and pearson correlation. Results: 15.6% of the rural elderly were completely edentulous and 54.7% were partially edentulous. Observed differences in distribution between the sampled elderly age groups were found to be statistically significant. Although 70.3% of the evaluated elderly actually required prosthodontic treatment, only 14.4% perceived the need to replace missing teeth. A small percentage of the elderly (18%) perceived a severe change in their diets due to tooth loss. Thirty three percent of them perceived a moderate change and 28% felt that there were no dietary changes because of tooth loss. Conclusions: It is essential to identify feasible strategies to provide primary dental health education and treatment to all rural elderly in the future. We suggest community dental health services as a general health need of the elderly rather than a special health need of the community.